Patient capacity and constraints in the experience of chronic disease: a qualitative systematic review and thematic synthesis - Boehmer, Kasey R.; Gionfriddo, Michael R.; Rodríguez Gutiérrez, René; Dabrh, Abd Moain Abu; Leppin, Aaron L.; Hargraves, Ian; May, Carl R.; Shippee, Nathan D.; Castaneda Guarderas, Ana; Zeballos Palacios, Claudia L.; Bora, Pavithra; Erwin, Patricia J.; et al. (2016)
Background: Life and healthcare demand work from patients, more so from patients living with multimorbidity. Patients must respond by mobilizing available abilities and resources, their so-called capacity. We sought to summarize accounts of challenges that reduce patient capacity to access or use healthcare or to enact self-care while carrying out their lives. Methods: We conducted a systematic review and synthesis of the qualitative literature published since 2000 identifying from MEDLINE, EMBASE, Psychinfo, and CINAHL and retrieving selected abstracts for full text assessment for inclusion. After assessing their methodological rigor, we coded their results using a thematic synthesis approach. Results: The 110 reports selected, when synthesized, showed that patient capacity is an accomplishment of interaction with (1) the process of rewriting their biographies and making meaningful lives in the face of chronic condition(s); (2) the mobilization of resources; (3) healthcare and self-care tasks, particularly, the cognitive, emotional, and experiential results of accomplishing these tasks despite competing priorities; (4) their social networks; and (5) their environment, particularly when they encountered kindness or empathy about their condition and a feasible treatment plan. Conclusion: Patient capacity is a complex and dynamic construct that exceeds “resources” alone. Additional work needs to translate this emerging theory into useful practice for which we propose a clinical mnemonic (BREWS) and the ICAN Discussion Aid. Abbreviations: BoT, Burden of treatment; BREWS, Biography, Resources, Environment, Work, Social; CASP, Critical appraisal skills programme; CuCoM, Cumulative complexity model